How multipurpose health workers spend time during work? results from a time-and-motion study from Puducherry - Nirmala Saravanan Narayanasamy; Subitha Lakshminarayanan; S Ganesh Kumar; Sitanshu Sekar Kar; Kalaiselvi Selvaraj (Wolters Kluwer Medknow Publications, 2018)
Background: A multipurpose health worker (MPHW) is the key functionary and the first contact person in a subcenter. This study explores the workload of MPHWs in the multifarious domains of their activities and also assesses their time utilization pattern. Methods: A time and motion study was conducted among 19 auxiliary nurse midwives (ANMs) and 10 HWs male (M) from six selected primary health centers of Puducherry. Participants self-reported their daily activities on a time measurement sheet for 6 days in a week. Data were entered in EpiData software and analyzed using Excel. Calculations are based on a total of 646 and 340 person-hours of observation by ANMs and HWs (M), respectively. Results: Time utilization pattern revealed that ANMs spent half of their time on maternal and child health activities. HWs (M) utilized 45% of their time for vector control programs and 11% for other programs. Documentation constituted nearly 16% and 10% time spent by ANMs and HWs (M), respectively. Other activities that constituted multipurpose workers' time utilization include traveling (8-10%), patient education (5-10%) and personal activities (6-12% ). The proportion of time spent in community activities was around 54% by HWs (M) and 32% by ANMs. Observations on self-reporting were comparable with that of participant observations. Conclusions: This study reflects the workload in different domains of MPHWs' activities and the "multipurpose" nature of their work, relevance of their job responsibilities in the context of national programs, and changing profile of their job.